Priority Programs Village Community Empowerment In Achievement Sustainable Development Goals (SDGs) in the Regency Bengkalis - Devi Deswimar; Ari Nurwahidah (Yayasan Riset dan Pengembangan Intelektual, 2025)
Village community empowerment is a strategic priority in reducing poverty in Bengkalis Regency, Riau Province. Bengkalis Regent Regulation Number 74 of 2021 mandates the strengthening of village institutions—such as BUMDes, LPM, PKK, and Posyandu—as key drivers for achieving Sustainable Development Goals (SDGs). The Community and Village Empowerment Office implements various training and capacity-building programs to enhance community independence through improved knowledge, skills, behavior, and the effective use of local resources. This study employs a qualitative descriptive approach to explore government officials’ and community members’ perceptions and experiences in implementing sustainable development through priority empowerment programs. The findings show that SDGs achievement in 2022 reached an average of 90% across assessed indicators, supported by active participation of village governments and communities, an increasing number of independent villages, and the growth of Village-Owned Enterprises. PKK and Posyandu activities also show significant improvement. Despite these achievements, challenges persist, including limited human resource capacity in managing local institutions, low productivity of BUMDes, and weak organizational capacity within village governance structures, particularly LPM.